Optimalisasi Budaya Sekolah melalui Strategi Integratif Pembelajaran PAI Berbasis Karakter - Yussuf Daffa Rosyidhaq; Nur Fayi’ Roudhoh Firdaus; Ummi Faaza Tsaqifah; Moh. Faizin (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Optimizing school culture is a crucial strategy for creating a learning environment conducive to students' character formation and moral development. This study aims to analyze integrative strategies for character-based Islamic Religious Education (PAI) in optimizing school culture, as well as to identify the supporting factors and challenges associated with their implementation. A qualitative approach utilizing library research methods was employed. Data were gathered from various relevant scholarly sources and analyzed using content analysis techniques, involving processes of data reduction, categorization, and conclusion drawing. The study reveals three primary implementation strategies: 1) integrating Islamic character values ​​into instructional materials, such as syllabi and lesson plans; 2) internalizing these values ​​through educators serving as role models and the habitual practice of religious activities within the school environment; and 3) fostering a religious school culture through policies and support from the school principal. Supporting factors include the commitment of the entire school community and the availability of facilities for religious observance, while the primary challenge lies in the lack of alignment between the values ​​implemented at school and those found in the students' family and community environments. Based on the analysis of the literature, integrating PAI instruction with school culture has the potential to enhance students' discipline, integrity, and religiosity. Therefore, more intensive partnerships between schools and parents are required to ensure that character cultivation continues sustainably in both the school and home environments.